Transmission of Eclipse Calculation Science: From the Wabkanawi Annular Eclipse Prediction to Adaptation of Calculation in the Archipelago - Rahmawati, Naili; Nurussaadah, Annisa; Firman, Jauharotul Maknunah; Aliyah, Fatimah Nur (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
Annular eclipses, in the discussion of classical Islamic astronomical treaties in Nusantara, do not appear as a separate natural phenomenon. We already know that the astronomical tables in these books refer to Ulugh Beg’s Zij Sultani in the 15th century AD. This raises the question of whether earlier astronomical traditions did not recognize annular eclipses. In fact, history records that the occurrence of annular solar eclipses had been successfully predicted since the 13th century AD by a Muslim astronomer from Iran known as Wabkanawi. This discrepancy then prompted researchers to explore how this chain of knowledge did not reach classic Islamic astronomical tradition. The research method used was a literature study with qualitative descriptive analysis. The findings of this research indicate that the science of calculation that reached the Indonesian archipelago had been adapted to religious traditions. The eclipse calculations taught were those needed for practical purposes for worship. In this case, annular eclipses have the same legal implications as partial eclipses, so they are considered unnecessary to calculate.